Tracking of the beat-to-beat blood pressure changes by the Caretaker physiological monitor against invasive central aortic measurement. Issue 1 (23rd September 2021) - Kwon, Younghoon; Stafford, Patrick L.; Baruch, Martin C.; Kim, Sung-Hoon; Cho, Yeilim; Mazimba, Sula; Gimple, Lawrence W.
Abstract : Objective: There is an unmet need for noninvasive continuous blood pressure (BP) monitoring technologies in various clinical settings. Continuous and noninvasive central aortic BP monitoring is technically not feasible currently, but if realized, would provide more accurate and real-time global hemodynamic information than any form of peripheral arterial BP monitoring in an acute care setting. As part of our efforts to develop such, herein we examined the tracking correlation between noninvasively-derived peripheral arterial BP by Caretaker device against invasively measured central aortic BP. Methods: Beat-to-beat BP by Caretaker was recorded simultaneously with central aortic BP measured in patients undergoing cardiac catheterization. Pearson's correlation was also derived for SBP and DBP. A trend comparison analysis of the beat-to-beat BP change was performed using a four-quadrant plot analysis with the exclusion zones of 0.5 mmHg/s to determine concordance, (i.e. the direction of beat-to-beat changes in SBP and DBP). Results: A total of 47 patients were included in the study. A total of 31 369 beats representing an average of 17.3 min of recording were used for analysis. The trend analysis yielded concordances of 84.4 and 83.5% for SBP and DBP, respectively. Respective correlations (Pearson's r ) for SBP and DBP trends were 0.87 and 0.86 ( P  < 0.01). Tracking of beat-to-beat BP by Caretaker showed excellent concordance and correlation in the direction and the degree of BP change with central aortic BP, respectively. Conclusion: This study supports the satisfactory performance of the Caretaker device in continuous tracking of central aortic BP beat-to-beat BP and provides a basis to develop an algorithm for absolute central aortic BP estimation in the future.